Business Responsibility and Sustainability Reporting: A Way Forward for Indian Corporate Disclosure: Business Responsibility and Sustainability Reporting in India - Debnath, Pranesh; Kanoo, Rishav (Journal of Commerce and Trade, 2022)
Business Responsibility and Sustainability Reporting (BRSR) is reporting from an Environmental, Social and Governance (ESG) perspective, and is intended to enable businesses to engage more meaningfully with their stakeholders. It will encourage businesses to go beyond regulatory financial compliance and report on their social and environmental impacts. The BRSR will be applicable to the top 1000 listed entities (by market capitalization), for reporting on a voluntary basis for FY 2021-22 and from FY 2022-23 on a compulsory basis. The ESG goals are sets of standards for a company’s operations that force companies to follow better governance, ethical practices, environment-friendly measures and social responsibility. Sustainability reporting will improve corporate reputation, build consumer confidence, increase innovation, and even improvement of risk management. The environmental criteria of BRSR will consider how a company performs as a steward of nature. Social criteria will take care of how the company manages relationships with employees, suppliers, customers, and the communities where it operates. Finally, the governance aspects will deal with a company’s leadership, executive pay, audits, internal controls, and shareholder rights. While the recommendations spell out elaborate content for companies that were already covered, the real challenge will also be for those who are absolutely new to this reporting requirement. The actual filling and filing of BRSR procedures have yet to be resolved and looking at the list of details, it's clear that quantifying and qualifying data to fit the reporting format is difficult for businesses. Classification-JEL: M14, M41, M48, G34, G38